Measuring the 'new balance of rights and responsibilities' in labor market policy: A quantitative overview of activation strategies in 20 OECD countries - Carlo Michael Knotz (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2012)
Labor market policies have been re-configured during the activation turn in labor market policy-making in the 1990s. This included restricting behavioral requirements for job seekers and benefit claimants, but also improving services (e.g. better placement services). In a nutshell, the rights and responsibilities of jobseekers and labor market participants were re-balanced. To date, there is is no indicator that could capture this in a quantitative way. This paper sets out to fill this gap. Using a number of quantitative indicators for 20 core OECD countries, it is shown what instruments countries use and how they balance instruments that either enforce labor market participation or enable to participate. It is shown that countries are overall rather similar with regard to the degree of enforcement (responsibilities), but differ with regard to the support (rights) they offer. Despite similarities and differences transcending welfare regimes, three worlds of activation can be distinguished. – – Im Zuge des activation turn wurden während der 1990er Jahre zahlreiche Arbeitsmarktreformen durchgeführt. Dies umfasste strengere Verhaltensregeln für Arbeitslose und Leistungsbezieher, aber auch Verbesserungen von Sachleistungen (bspw. verbesserte Arbeitsvermittlung). Kurz gesagt, die Rechte und Pflichten von Arbeitslosen sowie Personen auf dem Arbeitsmarkt wurden neu austariert. Derzeit gibt es nur wenig Möglichkeiten, dies quantitativ zu erfassen. Dieses Papier stellt einen Versuch dar, diese Lücke zu füllen. Unter Verwendung einer Reihe von quantitativen Indikatoren für 20 Kern-OECD Länder wird gezeigt, welche Instrumente von diesen Ländern in welchem Umfang verwendet werden, und in welchem Verhältnis fördernde und fordernde Instrumente stehen. Es wird gezeigt, dass sich die Länder bezüglich des Ausmaßes des Forderns (Pflichte) generell recht ähnlich sind, jedoch deutliche Unterschiede beim Umfang des Förderns erkennbar sind. Trotz Ähnlichkeiten und Unterschiede über die Grenzen der Wohlfahrtsstaats-Regime hinweg können drei Welten der Aktivierung Arbeitsloser unterschieden werden.
Keywords: 300